Specific surface area changes and functional potential exploration of Pleurotus pulmonarius under ultrasonic frequency control - Hangyu Fan; Jinlin Jiang; Huaihai Dong; Jinqing Hu; Wenjun Chen; Yingjie Pan; Yong Zhao; Haiquan Liu (Food Chemistry: X)
This article explores the changes in the specific surface area of Pleurotus pulmonarius under the control of different ultrasonic frequencies, analyzes the changes in flavor substances of P. pulmonarius and explores its functional nutritional potential. The results show that within a certain range, the specific surface area and pore size increase with the increase of ultrasonic waves, which has a significant effect on the release of flavor substances of P. pulmonarius and also affects its ability to adsorb and release substances. Therefore, controlling the specific surface area and pore structure of P. pulmonarius by ultrasonic frequency can make P. pulmonarius more effectively absorb nutrients in the surrounding environment and improve its nutritional value and availability.